Current Trends in Breast Augmentation: An International Analysis. (7th June 2017) - Heidekrueger, Paul I; Sinno, Sammy; Hidalgo, David A; Colombo, Martín; Broer, P Niclas
Abstract: Background: Breast augmentation surgery remains the most frequently performed aesthetic surgical procedure worldwide. However, many variations exist regarding preoperative planning, surgical management, and postoperative care. Objectives: The goal was to evaluate current trends and practices in breast augmentation, with a focus on international variability. Methods: A questionnaire was sent to over 5000 active breast surgeons in 44 countries worldwide. The survey inquired about current controversies, new technologies, common practices, secondary procedures, and surgeon demographics. The findings and variations were evaluated and correlated to evidence-based literature. Results: There were a total 628 respondents equaling a response rate of approximately 18%. While certain approaches and common practices prevail also on an international basis, there exist several geographic controversies. For example, while almost fifty percent of surgeons in the United States and Latin America never use anatomically shaped implants, in Europe and Oceania most surgeons use them. Similarly, in Latin America, Europe, Asia, and Oceania, over 80% of surgeons use silicone implants only, whereas in the United States only 20% use them − meanwhile US surgeons use the largest implants (78% > 300 cc). Internationally dominant practice preferences include preoperative sizing with silicone implants, as well as the use of inframammary incisions and partial submuscular pockets. Conclusions: Significant differences exist when comparing most common surgical breast augmentation approaches on an international basis. While certain techniques seem to be universal standards, there still remain several controversies. Further standardizing this most common aesthetic surgical procedure according to evidence-based guidelines will help to improve outcomes.